Land‐use intensification effects on functional properties in tropical plant communities. Issue 1 (January 2016) - Carreño‐Rocabado, Geovana; Peña‐Claros, Marielos; Bongers, Frans; Díaz, Sandra; Quétier, Fabien; Chuviña, José; Poorter, Lourens
Abstract: There is consensus that plant diversity and ecosystem processes are negatively affected by land‐use intensification (LUI), but, at the same time, there is empirical evidence that a large heterogeneity can be found in the responses. This heterogeneity is especially poorly understood in tropical ecosystems. We evaluated changes in community functional properties across five common land‐use types in the wet tropics with different land‐use intensity: mature forest, logged forest, secondary forest, agricultural land, and pastureland, located in the lowlands of Bolivia. For the dominant plant species, we measured 12 functional response traits related to their life history, acquisition and conservation of resources, plant domestication, and breeding. We used three single‐trait metrics to describe community functional properties: community abundance‐weighted mean (CWM) traits values, coefficient of variation, and kurtosis of distribution. The CWM of all 12 traits clearly responded to LUI. Overall, we found that an increase in LUI resulted in communities dominated by plants with acquisitive leaf trait values. However, contrary to our expectations, secondary forests had more conservative trait values (i.e., lower specific leaf area) than mature and logged forest, probably because they were dominated by palm species. Functional variation peaked at intermediate land‐use intensity (high coefficient of variation and low kurtosis), which included secondary forest but, unexpectedly, also agricultural land, which is an intensely managed system. The high functional variation of these systems is due to a combination of how response traits (and species) are filtered out by biophysical filters and how management practices introduced a range of exotic species and their trait values into the local species pool. Our results showed that, at local scales and depending on prevailing environmental and management practices, LUI does not necessarily result in communities with more acquisitive trait values or with less functional variation. Instead of the widely expected negative impacts of LUI on plant diversity, we found varying responses of functional variation, with possible repercussions on many ecosystem services. These findings provide a background for actively mitigating negative effects of LUI while meeting the needs of local communities that rely mainly on provisioning ecosystem services for their livelihoods.